SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KINERJA PERAWAT TERBAIK DI KLINIK AMANAH DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Fatkhurrochman Fatkhurrochman; Muhammad Abdul Muin (Politeknik Bisnis Indonesia, 2022)
The Department of Health is a health institution that is engaged in providing health services for the community. Amanah Clinic is one of the maternity clinics in Magelang City that serves various types of diseases and complaints from patients and the community. Medical personnel are the spearhead in improving clinical services. In developing superior medical personnel, Amana Clinic makes a selection program for the best nurses based on criteria such as: performance, discipline, education level and attitude. The old system that is running still has weaknesses because it is only based on 1 criterion (number of attendance) and ignores other criteria. The system causes injustice in the selection process. The purpose of this study was to design a decision support system for selecting the best nurse using the Simple Additive Weighting method. This method was chosen because it can perform a ranking process based on criteria and weights and is able to determine the best alternative. System design with Context Diagram, HIPO, DAD and ERD. Application results are nurse reports, overall selection and selection of the best nurses. The results of the functionality test are proven to be successful and the Validity Test has been proven to be 100% valid.